POTENSI TO’TOAN (Tacca leontopetaloides (L.) O.Kuntze) SEBAGAI BAHAN PANGAN DI PULAU KANGEAN, JAWA TIMUR - Siti Susiarti (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Tacca leontopetaloides (L.) O. Kuntze has the potential as food alternative source from its tubers and therefore selected for food diversification study.This research was conducted on Kangean island using open-ended interview methods,field observations,purposive sampling and chemical analysis.Tacca leontopetaloides still not much known and utilizated by the local people in East Java.The plant has different local names for each region, such as in Madura they known as